2020
DOI: 10.3390/molecules25173815
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding of Cisplatin to p22phox, an Endoplasmic Reticulum (ER) Membrane Protein, Contributes to Cisplatin Resistance in Oral Squamous Cell Carcinoma (OSCC) Cells

Abstract: Prolonged treatment with cisplatin (CDDP) frequently develops chemoresistance. We have previously shown that p22phox, an endoplasmic reticulum (ER) membrane protein, confers CDDP resistance by blocking CDDP nuclear entry in oral squamous cell carcinoma (OSCC) cells; however, the underlying mechanism remains unresolved. Using a fluorescent dye-labeled CDDP, here we show that CDDP can bind to p22phox in both cell-based and cell-free contexts. Subsequent detection of CDDP-peptide interaction by the Tris-Tricine-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The mechanism of cisplatin resistance has been widely discussed and unveiled, such as DNA repair proteins and stress proteins [11]. Many drug targets were reported to mediate resistance of OSCC cells to cisplatin, including excision repair cross-complementation group 1 protein [22], endoplasmic reticulum membrane protein p22phox [23], NF-κB [24], tongue cancer resistance-associated protein 1 (TCRP1) [25], and miR-21 [26]. The p22phox may directly bind to small molecule anticancer drugs like platinum, and increase resistance of cancer cells to platinum drugs [27].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of cisplatin resistance has been widely discussed and unveiled, such as DNA repair proteins and stress proteins [11]. Many drug targets were reported to mediate resistance of OSCC cells to cisplatin, including excision repair cross-complementation group 1 protein [22], endoplasmic reticulum membrane protein p22phox [23], NF-κB [24], tongue cancer resistance-associated protein 1 (TCRP1) [25], and miR-21 [26]. The p22phox may directly bind to small molecule anticancer drugs like platinum, and increase resistance of cancer cells to platinum drugs [27].…”
Section: Discussionmentioning
confidence: 99%
“…It can induce oxidative stress damage (40). Hung et al reported that the overexpression of p22phox sequestered cisplatin and caused defective cisplatin entry into the nucleus in oral squamous cell carcinoma (41). CYBA mutation or p22phox expression was closely related to insulin resistance in metabolic syndrome by affecting oxidative stress (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…To date, cisplatin-or paclitaxel-based chemotherapy, combined with other chemotherapeutic agents, remains the first-line treatment for ovarian cancers [28]. Recent reports have shown that p22 phox is a cisplatin-resistant gene that suppresses DNA adduct-induced apoptosis by blocking cisplatin uptake into the nucleus and activating the PI3K/Akt pathway [13]. Our study found that interfering with p22 phox function could enhance the drug sensitivity of ovarian cancer cells to cisplatin or paclitaxel and thus provides a new concept for the treatment of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, downregulation of p22 phox inhibited Akt-dependent phosphorylation of tuberin and stabilized tuberin protein levels in VHL-deficient renal carcinoma cells [11]. Furthermore, p22 phox has been reported to function as a cisplatin-resistant factor that suppresses DNA adduct-induced apoptosis by blocking cisplatin uptake into the nucleus and activating the phosphatidylinositol 3-kinase (PI3K)/Akt pathway in oral squamous cell carcinoma [12,13]. However, whether the expression of p22 phox occurs in the different epithelial ovarian cancer types and the role of p22 phox in epithelial ovarian cancer progression has not been established.…”
Section: Introductionmentioning
confidence: 99%